Controlled in vitro degradation behavior of highly oriented long‐chain‐branched poly(lactic acid) produced by solid‐phase die drawing. Issue 7 (12th March 2019) - Li, Ruiguang; Li, Jiafeng; Zhao, Xiaowen; Ye, Lin; Coates, Phil; Caton‐Rose, Fin
Abstract: Highly oriented long‐chain‐branched poly(lactic acid) (LCB‐PLA) was fabricated through solid‐phase die drawing technology, and the in vitro degradation behavior of the oriented samples in phosphate‐buffered saline (PBS) was studied. During degradation, the weight retention and molecular weight for both PLA and LCB‐PLA increased with the increase of draw ratio. Moreover, the degradation autocatalytic effect was delayed, and the deterioration of mechanical strength was reduced by orientation, which was beneficial for controlling the degradation degree and decay rate of strength for PLA as bone fixation materials. The influence mechanism of orientation on the in vitro degradation of PLA was explored. The degradation of PLA in PBS was ascribed to the hydrolytic degradation of ester bonds on the molecular chain. By orientation, a dense microfibrillar crystalline structure formed both on the surface and inside of PLA samples, limiting the diffusion and absorption of PBS molecules into the PLA matrix effectively, inhibiting the hydrolytic degradation of ester bonds, and thus delaying the deterioration of mechanical properties of PLA. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2019.